2017
DOI: 10.1097/igc.0000000000000892
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression in Premalignant and Malignant Trophoblasts From Gestational Trophoblastic Diseases Is Ubiquitous and Independent of Clinical Outcomes

Abstract: We confirm that PD-L1 is constitutively expressed in all GTD premalignant and malignant trophoblast subtypes, independently from FIGO score, chemoresistance, or fatal outcomes, thereby suggesting a crucial role for PD-L1 in the development and tolerance of GTD. Assessment of anti-PD-L1 drug in GTD patients has been activated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 23 publications
4
50
0
1
Order By: Relevance
“…Consistent with previous studies, our results confirmed the ubiquitous and strong expression of PD‐L1 in GTN. Additionally, we found that PD‐L2 protein was positive in 87.5% of GTN samples and that it correlated significantly with PD‐L1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies, our results confirmed the ubiquitous and strong expression of PD‐L1 in GTN. Additionally, we found that PD‐L2 protein was positive in 87.5% of GTN samples and that it correlated significantly with PD‐L1.…”
Section: Discussionsupporting
confidence: 92%
“…Programmed cell death ligand 1 (PD‐L1) is expressed in both placental trophoblasts and GTN, suggesting that this protein is involved in maternal immune tolerance and tumour immune escape. PD‐L1 belongs to the B7 family of immunoregulatory molecules, and has been extensively studied in human malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…This immune checkpoint blockade therapy, justified by a strong expression of PD-L1 in GTN, was recently approved in Merkel cell carcinoma with an excellent tolerance profile. 18,19 Efficacy, toxicity, patients inconvenience, and treatment cost of these promising alternatives need to be prospectively compared.…”
Section: Discussionmentioning
confidence: 99%
“…[113][114][115] Programmed death ligand 1 (PD-L1) is strongly expressed by GTN. 116,117 Outcomes were recently reported for 4 patients with drug-resistant GTN who received pembrolizumab, including 2 with metastatic choriocarcinoma and 2 with metastatic PSTT or mixed PSTT/ETT. 118 All patients had tumors with high levels of PD-L1 expression.…”
Section: Salvage Chemotherapymentioning
confidence: 99%